2007
DOI: 10.1111/j.1365-2516.2006.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Is primary postpartum haemorrhage a good predictor of inherited bleeding disorders?

Abstract: A study was conducted to evaluate the value of screening for inherited bleeding disorders in women with primary postpartum haemorrhage (PPH). Over a 2-year period, women identified to have PPH (defined as >500 mL blood loss for spontaneous vaginal delivery, >700 mL for instrumental deliveries and >1000 mL for caesarean sections within 24 h of delivery) were invited to participate in this study testing for a possible underlying bleeding disorder at 3-9 months post-delivery. Women known to have an inherited blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…21 Furthermore, we found that the majority of women was diagnosed with low VWF or mild VWD type 1 (9/16, 56%). In line with our results, one study also mentioned the value of a Bleeding Assessment Tool, as the only woman diagnosed with a bleeding disorder was also the only patient who reported more than two additional bleeding symptoms.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…21 Furthermore, we found that the majority of women was diagnosed with low VWF or mild VWD type 1 (9/16, 56%). In line with our results, one study also mentioned the value of a Bleeding Assessment Tool, as the only woman diagnosed with a bleeding disorder was also the only patient who reported more than two additional bleeding symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…21 In contrast to our study, this study included women with blood loss of ≥500 mL for spontaneous vaginal deliveries, ≥700 mL for instrumental deliveries and ≥1000 mL for caesarian sections, to define a group of women more likely to have abnormal coagulation. 21 In contrast to our study, this study included women with blood loss of ≥500 mL for spontaneous vaginal deliveries, ≥700 mL for instrumental deliveries and ≥1000 mL for caesarian sections, to define a group of women more likely to have abnormal coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…PPH is multifactorial in nature and the prevalence of undiagnosed bleeding disorders in women presenting with PPH is unknown. In a study of 50 women with primary PPH screened for underlying bleeding disorders (VWD and FXI deficiency) 3 to 9 months after delivery, only one woman was diagnosed with VWD, suggesting that primary PPH is not a helpful discriminator to screen for these bleeding disorders . Further larger studies are required to fully answer this question.…”
Section: Inherited Bleeding Disordersmentioning
confidence: 99%
“…In a study of 50 women with primary PPH screened for underlying bleeding disorders (VWD and FXI deficiency) 3 to 9 months after delivery, only one woman was diagnosed with VWD, suggesting that primary PPH is not a helpful discriminator to screen for these bleeding disorders. 39 Further larger studies are required to fully answer this question. Bleeding assessment tools, [40][41][42] which catalog the bleeding history of patients to evaluate the likelihood of an underlying bleeding disorder have not yet been validated in women who have experienced PPH.…”
Section: Can Pph Be An Indicator Of An Unidentified Bleeding Disorder?mentioning
confidence: 99%
“…12, 2224 Other congenital coagulation disorders, including Factor II, VII, X, XI deficiencies and carriage of hemophilia A and B are rare, but have also been associated with excess bleeding with delivery. 12, 2426 While based on small studies, the prevalence of undiagnosed coagulation disorders in the general population of patients with PPH is low, 27, 28 and further study is needed to ascertain whether this may not pertain to the population of women that experience recurrent PPH.…”
Section: Commentmentioning
confidence: 99%